Requirements for implementing strategic cost management methods in Algerian economic institutions (Journal of Economic Additions, 2026)
This study aims to explore the strategic management of costs and the requirements for its implementation in Algerian economic institutions. A field study was conducted on a group of economic institutions located in a specific region, utilizing a questionnaire as the primary tool for data collection. The findings reveal that, although the institutions possess the necessary capabilities to adopt these methods, certain obstacles hinder their effective application.Jel Classification Codes: O32, G32.
Keywords: Cost management; Strategic management; Strategic analysis tools.